Ecological Education and Awareness – The Importance of Ecological Education in Schools and Communities - Ismailov Ulug‘bek O‘ktamboy o‘g‘li, Sultanov Akbarbek Mansurbek o‘g‘li, Abdujabborova Osiyo Abdurazzoq qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The mentioned article provides information about the significance of environmental education in schools and various communities. Additionally, the article discusses environmental issues and their various types, along with information related to environmental awareness.